Epistemic Responsibility, Rights and Duties During the COVID-19 Pandemic. (2nd November 2022) - Karimov, Artur; Lavazza, Andrea; Farina, Mirko
ABSTRACT: We start by introducing the idea of echo chambers. Echo chambers are social and epistemic structures in which opinions, leanings, or beliefs about certain topics are amplified and reinforced due to repeated interactions within a closed system; that is, within a system that has a rather homogeneous sample of sources or people, which all share the same attitudes towards the topics in question. Echo chambers are a particularly dangerous phenomena because they prevent the critical assessment of sources and contents, thus leading the people living within them to deliberately ignore or exclude opposing views. In the second part of this paper, we argue that the reason for the appearance of echo chambers lies in the adoption of what we call 'epistemic vices'. We examine which vices might be responsible for their emergence, and in doing so, we focus on a specific one; 'epistemic violence'. In assessing and evaluating the role of this epistemic vice, we note that it can be triggered by epistemic contexts characterized by high stakes that may turn ordinary intellectual virtues (such as skepticism) into vices (such as denialism). In the third part of this contribution, we suggest a way to deal with echo chambers. The solution focuses on advocating a responsibilist pedagogy of virtues and vices that -we claim- might be capable of preventing their emergence.